Experimental investigation of nanographene mixed in the copper electrodes for electrical discharge machining - Osama Sabbar; Ali Khleif; Baraa Albaghdadi (Engineering and Technology Journal)
Nanotechnology in electrode manufacturing is a new technique to enhance the machinability of materials that are difficult to machine using electrical discharge machining (EDM). Since the wear of electrodes in the EDM process usually has a high effect on the process performance, thus it is important to conduct a study to reduce the tool wear rate (TWR) and increase the Material removal rate (MRR). This study aims to improve the operation performance of nanomaterial graphene in the electrode industry. In this experimental work, single-layer nanographene with a concentration of (2%wt) was mixed into a copper matrix using the stir-casting method for machining AISI 1005 Carbon Steel. The parameters selected are discharge current Ip (20, 30, and 40 A), pulse on time Ton (100, 200, and 300 μs), and pulse off time Toff (100, 150, and 200 μs). All the experimental runs were conducted using Design Expert 13 software at three levels and ANOVA for the statistical study. The results of this study manifested that the EDM performance was significantly enhanced by utilizing the powder of nanographene and enhancement through the performance measures of TWR and MRR improved by 15.10% and 29.67%, respectively, and enhanced the economic efficiency of this technology through the improved mechanical and electrical properties. Finally, scanning electron microscopy (SEM) was used to examine the effect of nanographene on the machined surface quality. The surface obtained from the copper electrode elucidated more surface flaws compared to the electrode mixed with nanographene powder.